Ideas for integrating meaningful immediate repetition tasks in the English as an additional language classroom: promoting fluency - Zaccaron, Rafael (BELT - Brazilian English Language Teaching Journal, 2019)
Although repetition is at the core of many different approaches to language learning, either implicitly or not, using this pedagogic practice in the additional language classroom is still negatively perceived by some teachers (Bygate and Samuda, 2005). For contemporary research, on the other hand, the use of repetition is not incongruous with communicative additional language teaching approaches that bring the use of tasks to the forefront. The use of immediate repeated tasks can benefit learners because it allows the possibility of repeating slightly altered tasks in a meaningful way. Bearing this in mind, this paper describes three immediate repetition tasks that focus on the speaking skill aiming at developing both fluency and accuracy. All are inherently suited for the additional language classroom and can be easily adapted to better suit specific contexts.